2013
DOI: 10.4293/108680812x13517013317671
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Liver Resection: Initial Experience With Three-Arm Robotic and Single-Port Robotic Technique

Abstract: Robotic liver surgery was found to offer advantages not inherent in conventional laparoscopic liver resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 36 publications
(33 reference statements)
0
19
0
1
Order By: Relevance
“…In case of overlapping populations, the most recent or most informative studies were included in the systematic review (Supplemental Table S2). From the 803 records retrieved, 31 studies were finally deemed eligible, incorporating a total of 1148 patients. The majority of studies were from Europe (14/31), followed by Asia (10/31) and the USA (7/31).…”
Section: Resultsmentioning
confidence: 99%
“…In case of overlapping populations, the most recent or most informative studies were included in the systematic review (Supplemental Table S2). From the 803 records retrieved, 31 studies were finally deemed eligible, incorporating a total of 1148 patients. The majority of studies were from Europe (14/31), followed by Asia (10/31) and the USA (7/31).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 29 articles were included and are presented in Table . The four conversions on 70 patients reported as “Giulianotti et al” were part of our series and detailed as “present series” at the end of the table.…”
Section: Resultsmentioning
confidence: 99%
“…Robotic MIS hepatectomy as a field is moving past its infancy. Nota et al (12) recently reported a collected series analysis of the 12 best studies up to 2015 (7,8,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). There is no doubt that hemi-hepatectomies can be performed with safety by the robotically-assisted approach (7,8).…”
Section: Discussionmentioning
confidence: 99%